CHARACTERIZATION OF SHALE GAS WITH GEOCHEMICAL AND INTEGRATED PETROGRAPHY ANALYSIS: CASE STUDY BELUMAI AND LOWER BAONG FORMATION, NORTH SUMATRA BASIN - Adi Hartomo, Dimas
Indonesia has a great potential shale gas resource. North Sumatra Basin is considered to be one of basin that have organic-rich shale with high value for shale gas prospect. Geochemical, petrography, and brittleness index parameters are important information for the success of shale gas exploration. The research location is in the southeastern part of the North Sumatra Basin which is in the Langkat Subbasin. Belumai and Lower Baong Formation have shale litology that suitable as target for shale gas exploration. The research datas collected from one of the wellbore in Langkat Subbasin. These datas are analyzed to determine its characteristics of quantity, quality, maturity of organic matter, litology, types of clay minerals, and brittleness index of the formation. Geochemical analysis consists of TOC (Total Organic Carbon), Rock-Eval pyrolysis, vitrinite reflectance, and TAI (Thermal Alteration Index). Integrated petrography analysis consists of thin section analysis, XRD (X-Ray Diffraction), and SEM (Scanning Electron Microscope). Brittleness index analysis through the result from quantitative XRD (X-Ray Diffraction) and TOC. Based on the geochemical analysis results, Belumai and Lower Baong Formation have quantity in poor to well category. With organic matter quality as type III and IV kerogen where dominant produce gas and for the maturity level lies on early mature to late mature. Based on the petrography analysis result, Belumai Formation consist of calcareous sandy mudstone litology and Lower Baong Formation consists of quartz claystone, shale, and calcareous claystone litology. Based on the XRD and SEM result shows that Belumai Formation have types of clay mineral in form of illite, kaolinite, and chlorite. For Lower Baong Formation have types of clay mineral in form of illite, kaolinite, chlorite, and illite - smectite. Interpretation of depositional environment of Belumai Formation is in the shallow marine in form the lagoon environment while for Lower Baong Formation deposited in the deep marine environment. The brittleness index value of Belumai Formation is categorized in less brittle – brittle and Lower Baong Formation is categorized in less ductile – brittle. The result of brittleness index value from Lemigas’s equation shows more positive value. Based on the comparison results between quantity, quality, and brittleness index with success parameters of gas shales exploration, Belumai Formation and Lower Baong Formation are less suitable to be nonconventional gas bearing shale.